ADAPTIVE SCHEDULING: APPLYING AI AND MACHINE LEARNING TO OPTIMIZE PROJECT TIMELINES AND RESOURCE - Chauhan, Neeraj (International Journal of Engineering Technologies and Management Research, 2025)
This paper seeks to discuss how project management is an ever-evolving activity due to the changing nature of the business environment, and proper techniques must be employed to enhance timelines and resources management. This study investigates the utilisation of Artificial Intelligence (AI) and Machine Learning (ML) in dynamic scheduling for project management. Another way is through the use of forecasting models, improvement of tuning algorithms, as well as real-time data analysis whereby through the time intervals, people are able to come up with new times and effective utilisation of resources. This paper explores and discusses numerous AI and ML approaches and studies the capability of these approaches for minimizing the number of delays and increasing the effectiveness of the management of the available resources to optimize overall project performance. In this paper, the applicability of these technologies for modifying the conventional scheduling systems is illustrated utilizing case studies and computerized simulations.